Characterization and Synthesis of This Comb Type Copolymer with Styrene Using A Macromonomer Containing Polyethylmethacrylate - Acikses, Aslisah; Sarac, Suleyman (Chem Soc Pakistan, 2019)
In this study, firstly 7-hydroxy-4-chloromethyl coumarin (CMHC) was synthesized from reaction of ethyl 4-chloroacetoasetate with resorcinol. Then, the poly(ethyl methacrylate) coumarin end grouped having hydroxyl (CEMA) was prepared by ethyl methacrylate with using (CMHC) as initiator by atom transfer radical polymerization (ATRP) method. A macromonomer (CMEMA) was synthesized from reaction of methacryloyl chloride and poly(EMA) ended coumarin having OH group (CEMA). Molecular brush of P(CMEMA-comb-%16St) was synthesized by reaction of macromonomer CMEMA and styrene by free radical polymerization method (SRP). The structures of the prepared macromonomer and molecular brush were characterized by FT-IR and H-1-NMR techniques. The thermal behavior of P(CMEMA-comb-%St) has been investigated by TGA, and the glass transition temperatures have been measured on DSC. The average molecular weights and polydispersity were determined by GPC. The dielectric behavior of P(CMEMA-comb-%16St) was investigated as a function of temperature and frequency. The intrinsic viscosity [eta] of P(CMEMA-comb-%16St) was determinated.
Keywords: Macromonomer; Comb Copolymers; Dielectric properties; Intrinsic Viscosity; Polymer